2022
DOI: 10.7860/jcdr/2022/57286.17124
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 70% Glycolic Acid Peel versus 30% Salicylic Acid Peel in the Treatment of Mild to Moderate Acne Vulgaris: A Retrospective Study

Abstract: Introduction: Chemical peels have become a useful modality in the management of acne in addition to topical and systemic medications. Studies done to evaluate the effectiveness of peels have compared only lower concentration of Glycolic Acid (GA) (35%) and Salicylic Acid (SA) peels. Higher concentrations of glycolic acid i.e., (70%) are reported to be safe and more effective than lower concentrations. Despite reported advantages of higher concentration of glycolic acid peel, no published data is available rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Due to its ability to exfoliate the skin and unclog pores, salicylic acid is a common constituent in numerous acne treatments. Research has shown that salicylic acid peels effectively treat mild to moderate acne vulgaris 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to its ability to exfoliate the skin and unclog pores, salicylic acid is a common constituent in numerous acne treatments. Research has shown that salicylic acid peels effectively treat mild to moderate acne vulgaris 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The advantageous effect of glycolic acid has been confirmed in relation to various skin problems connected to keratinization disorders. Glycolic acid peeling treatments affect the lightening of melasma and post-inflammatory hyperpigmentation, are an element of anti-acne therapy in adolescents and adults and reduce actinic or seborrheic keratosis [ 46 , 47 , 48 ]. Glycolic acid also improves the penetration of other exfoliants.…”
Section: Discussionmentioning
confidence: 99%
“…Both peels had comparable effectiveness. Salicylic acid peel demonstrated an advantage of achieving an earlier decrease in lesional count than the glycolic acid peel [83]. 2013) compared the efficacy and safety of 30% salicylic acid peels with Jessner's solution peels in treating mild-to-moderate facial acne.…”
Section: Comparative Studies That Used Glycolic Acid Versus Other Pee...mentioning
confidence: 99%